A survey of reported changes in diet and activity with the FreeStyle Libre flash glucose monitor: a pilot study. (1st February 2022) - Arnason, Terra; Cameron, Amanda; Nour, Munier; Inman, Mark; Mansell, Kerry
Abstract: Introduction: Flash glucose monitors (FGMs) are increasingly popular with people with diabetes. We aimed to see if the use of the FreeStyle Libre affected users' behaviours regarding dietary choices and exercise. Methods: An online questionnaire was developed using Voxco Survey Platform 2018 and was completed between 18 May and 14 August 2018. The questionnaire consisted of yes/no and 6‐point Likert scale questions to assess the effects of FGM on diet and exercise patterns. Anyone with diabetes who had been using the FGM for at least four weeks prior to study commencement was eligible to participate. Results: Forty‐one participants completed the questionnaire; the majority were < 18 years old (29/41; 70.7%), and had type 1 diabetes (37/41; 90.2%). As a result of using the FGM, 58.6% (17/29) of paediatric participants indicated they noticed specific foods affected their blood glucose levels that they were not previously aware of, and 31.0% (9/29) indicated that they changed their carbohydrate choices to lower glycaemic index foods. In all, 72.4% (21/29) of paediatric participants indicated that they felt more confident in participating in exercise, 20.7% (6/29) indicated that they initiated new exercise, and 13.8% (4/29) indicated that they increased their amount of exercise as a result of using the FGM. Conclusions: In this study of primarily paediatric patients, some participants reported improved confidence to participate in exercise, as well as making positive dietary changes as a result of using the FGM. Further study is required to confirm if the FGM may have positive and sustained effects on these parameters. Copyright © 2022 John Wiley & Sons.